Efecto del tipo de cobertura vegetal sobre las condiciones micro meteorológicas de dos hábitats, en una localidad del Valle Central, Costa Rica (ING) - Rodríguez N, Hernán; Hilje Q, Luko (Uniciencia, 1986)
Although vegetative cover does not markedly affect daily patterns of air temperature and relative humidity in a coffee and a pine plantation, it certainly affects the daily pattern of soil temperature. Yet, the soil microclimate does not seem to exert an important influence on soil-living organisms.